Predictive Microbiome Post-Bone Marrow Transplantation and Acute Graft versus Host Disease - Varghese, Chithra (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2023)
Haemopoietic stem-cell transplantation serves as one of the life-saving options for the management of refractory haematological malignancies and rarely for non-malignant conditions. The era of transplantation has significantly progressed due to the wider availability of suitable donors and better treatment options. However, there are several factors limiting the success of transplantation of which acute graft versus host disease continues to pose significant challenges. aGVHD is associated with reduced quality of life and contributes to one of the major causes of non-relapse-related mortality. There is growing evidence to suggest the role of microbiota in various inflammatory and metabolic conditions of which intestinal microbes and their genomic components merit special attention. The microbiota exerts their effects through local mucosal actions and systemically through their metabolites and enzymatic pathways. Previous studies have demonstrated the changes in the microbial diversity post-stem cell transplantation and their significance on the outcomes, including the risk of GVHD. The impact of this microbial shift on the transplant outcomes is independent of the patient and donor-related factors. Our study has evaluated the pre-transplant microbial changes in faecal samples of patients undergoing allogeneic stem cell transplantation and corresponding sibling transplant donors. Faecal microbial DNA analysis was carried out in the recipients and sibling donors from the samples collected prior to the pre-conditioning period. Furthermore, genomic sequencing of these microbial DNA was performed to investigate any shift in microbial composition and has been correlated with complications especially, the risk of aGVHD and survival following transplantation. With Random Forest Prediction models we were able to demonstrate the association between microbiome and the risk of aGVHD with an accuracy of more than 70%. We hypothesise that there would be a specific microbial readout in the faecal microbiome obtained from the patients and donors prior to transplantation which would be predictive of post-transplant complications and in particular acute GVHD. Our study has demonstrated specific changes in the pre-transplant microbial diversity which was associated with the risk of aGVHD and survival following transplantation. Further analysis has identified the activation of specific enzymatic pathways driving steroid responsiveness in aGVHD. Lower microbial diversity in the sibling donors was linked with severe GVHD in the corresponding recipients. From the study, it was evident that this microbial dysbiosis can occur weeks prior to stem cell infusions and affects the transplant outcomes which was independent of disease and treatment-related complications. Microbial diversity and richness have been increasingly identified in the pathogenesis of various inflammatory and metabolic disorders including the risk of GVHD. Our study shed light on the fact that lower microbial diversity pre-transplantation is associated with complications such as aGVHD and increased mortality. Modulating or replacing this microbiome would serve as a potential therapeutic target in the management of aGVHD and improving survival following transplantation. The impact of the donor microbial diversity on the severity of aGVHD will be crucial when selecting suitable donors for stem cell transplantation with an improved outcome.
APPROVED
Keywords: Bone Marrow Transplantation; Acute graft versus host disease; microbiome